Effects of simulated litter inputs on ecological niches and interspecific connectivity of alpine meadow plants - Lin, Weishan; De, Kejia; Xiang, Xuemei; Feng, Tingxu; Li, Fei; Wei, Xijie (Frontiers in Plant Science, 2025)
IntroductionPlant litter enters the soil as the main nutrient for alpine meadow ecosystems, and the amount of litter input has a significant effect on alpine meadow plant diversity, ecological niches, and interspecific connectivity.MethodsThe ecological niche width, ecological niche overlap and interspecific associations of alpine meadow species in the Sanjiangyuan area of the Qinghai-Tibetan Plateau were investigated using ecological statistical methods, and the competitive linkages between species and limited resources within the community and the stable coexistence among populations under different levels of plant litter inputs were explored.Results(1) Litter inputs could significantly increase the plant diversity and aboveground biomass of alpine meadows, and the species with the highest importance value was Kobresia humilis Clarke. (2) compared with the control, with the increase of litter inputs, the ecological niche widths of the major plant species and ecological niche overlap values were significantly increased. And the F2 treatment had 15 major species totaling 105 pairs, and there were 82 pairs of ecological niche overlap values ≥0.950, accounting for 78.1%. (3) The correlation analysis between species showed that the negative correlation between species decreased and then increased with the increase of litter input. There were 3 pairs with Ac ≥ 0.25 under F2.DiscussionA moderate amount of litter input (F2) is beneficial to the structural stability of alpine meadow ecosystems. Excessive litter inputs may break the original balance of alpine meadow ecosystems and affect plant growth strategies. This study lays a foundation for the conservation of vegetation diversity and long-term use of grassland resources in degraded alpine meadows on the Tibetan Plateau.